A giant choledochal cyst: A case reported from Tanzania. (April 2021) - Suleiman, Jamil M.; Msuya, David; Philemon, Rune; Sadiq, Adnan; Amsi, Patrick; Lodhia, Jay
Highlights: Choledochal cyst is a rare malformation of the common bile duct causing jaundice in the pediatric group. Diagnosis can easily be made using abdominal ultrasonography, hence a high degree of suspicion is needed among clinicians. Surgery, open or laparoscopic, remains the core management depending upon the availability of the resources and expertise. Abstract: Introduction: Choledochal cyst is a rare common bile duct malformation that usually presents in the pediatric group with abdominal pain, distension, and jaundice. The pathophysiology remains unclear for the cause, and surgery aims to restore biliary enteric drainage. Case presentation: We present a six-year-old female who presented with gradual abdominal distention associated with jaundice. Abdominal ultrasound was suggestive of choledochal cyst, and CT-scan confirmed the diagnosis. She was operated on successfully and fared well. Conclusion: Choledochal cysts are a rare entity of common bile duct malformations and should be considered as a differential diagnosis in the pediatric age group. Diagnosis can be easily made by non-invasive and in-expensive radiologic modalities like ultrasonography in resource-limited settings.